Prevention of Fraud in Sharia Banking in Indonesia through Implementation of Sharia Corporate Governance - Apriliani Astuti, M; Dewi Y Rozali, R; Cakhyaneu, A (KnE Social Sciences, 2019)
This research is motivated by the existence of fraud phenomenon that still occurs in sharia banking environment which in fact is based on Islamic principles in every activity. Based on data from ACFE (Association Of Certified Fraud Examiners) in 2016 shows that banks and financial institutions are the highest entities in the case of fraud. Sharia principles that are run by Islamic banks do not necessarily make Islamic banks to avoid fraud cases. Cases of fraud that many overwrite Islamic banks may be due to weak implementation of sharia corporate governance. The data in this research is obtained from Good Corporate Governance of syariah banking (BUS-UUS) period 2012-2016 using a quantitative approach. The result of research shows that the implementation of sharia corporate governance in syariah banking is categorized into three parts that are very good, good and good enough but from the implementation of sharia corporate governance is still not able to prevent fraud in sharia banking. This study has important implications, namely sharia banking must be balanced with the ability of good human resources because Islamic banks is a banking business that combines the principles of banking and Islamic principles. In addition, organizational culture and tone at the top can also be a lock to prevent fraud, Keywords: Sharia Corporate Governance, Fraud